Social-Economic Background of the Economic Digitalization in Indonesia - Nurul Infitah (Faculty of Islamic Economics and Business, State Islamic University of Kiai Haji Achmad Siddiq Jember, Indonesia, 2022)
Currently, almost all activities of the world community are facilitated by technological developments. Including in the economic field, technology emerges, so the world community calls it economic digitization. Economic digitization is all economic activities based on digital technology. This paper each indicator such as the ICT Development Index or the Information and Communication Technology Development Index (IP-TIK), the Global Innovation Index or the Global Innovation Index (IIG), the Networked Readiness Index or the Network Readiness Index (IKJ), Share of Households with Internet or Internet User Households (RTPI) and High-Technology Exports (% of manufactured exports) or High-Technology Exports (ETT). The data used is secondary data taken from BPS related to IP-TIK, IKJ, RTPI and ETT.